(untitled) (Genta Hredaya: Media Informasi Ilmiah Filsafat Hindu, 2024)
This paper aims to examine the general patterns that occurred in the dynamics of the political history of Banten’s government from the sultanate era, post-sultanate, to its establishment as a province as the material object of this discussion. The formal object is the philosophy of speculative history by borrowing the theory of patronage-clientelism and dynastic politics. This article uses a qualitative/literary research method with elements of the historical continuity method which is then analysed critically-reflectively by the author and presented descriptively. The results of the discussion found the thesis of the existence of a cyclical pattern that moves backwards in the political history of Banten’s government and the existence of patronage and political dynasties as historical driving factors that have a great influence on sultanate/government politics that determine the progress and decline of Banten. This thesis is strengthened by several arguments: First, that patronage-clientelism through a review of individual-group relations in Banten’s history proves that the figure of the sultan and his loyalists had a major influence in determining the glory and collapse of the Banten sultanate. Secondly, after the collapse of the sultanate until the establishment of Banten as a province, Banten lost a patron/political figure who was able to lead the Banten government with the spirit of the value of kebantenan/marwah that was once respected by the nations of the archipelago because only the romanticism of a glorious history remained. Third, since Banten separated into its own province in 2000 until now it has been greatly influenced by dynastic politics/familism in the typology of octopussy dynasties because those involved in this dynasty are not only direct blood relations but also other extended families (relatives) which has caused the political dynasty to take root and spread in Banten, but has no significant influence on the welfare and prosperity of the Banten people.